2001
DOI: 10.1021/op0102161
|View full text |Cite
|
Sign up to set email alerts
|

Practical Large-Scale Synthesis of 3,4-Isopropylidenedioxypyrrolidine Hydrotosylate:  Atom Economical Self-Hydrogenolysis of a Crystalline Borane−Benzylamine Adduct

Abstract: An efficient four-step sequence has been developed for the synthesis of 3,4-isopropylidenedioxypyrrolidine hydrotosylate starting from inexpensive N-benzylmaleimide. This approach features a novel N-debenzylation procedure that utilizes the corresponding borane-benzylamine complex as an internal hydrogen-transfer source. This palladium-catalyzed tandem protonolysis/hydrogenolysis allows cleavage of the boraneamine adduct and debenzylation in a single operation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
20
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 19 publications
0
20
0
Order By: Relevance
“…Many metals and metal complexes have been found to catalyse amine borane solvolysis (Table 2). [71][72][73][74][75][76][77][78][79][80] The recent focus in catalyst development has been on the use of non-precious metals. In two recent heterogeneous systems, catalyst morphology greatly affected catalytic activity.…”
Section: Metal-catalysed Solvolysismentioning
confidence: 99%
“…Many metals and metal complexes have been found to catalyse amine borane solvolysis (Table 2). [71][72][73][74][75][76][77][78][79][80] The recent focus in catalyst development has been on the use of non-precious metals. In two recent heterogeneous systems, catalyst morphology greatly affected catalytic activity.…”
Section: Metal-catalysed Solvolysismentioning
confidence: 99%
“…Hence, it is possible to increase the reaction yields by prolonging the reaction time. In this way, very acid-sensitive compounds like 53 (Scheme 16, equation 1), or very unreactive electron-deficient tetrasubstituted olefins like 55 (Scheme 16, equation 2) 58 are dihydroxylated in excellent yields.…”
Section: Dihydroxylation and Ketohydroxylationmentioning
confidence: 99%
“…5 Practical osmium free methods for cis-dihydroxylation of alkenes that avoid the need for excess amounts of oxidant are highly desirable, both in synthesis and for the large scale production of important building blocks, not least N-aryl and N-alkylmaleimides. 6 Furthermore, the cis-dihydroxylation of electron deficient alkenes such as N-alkyl-pyrrole-2,5-diones remains a major challenge with the more reactive ruthenium based catalysts systems employing NaIO 4 providing one of the few effective routes available to the cis-diol products. For example 1-benzyl-1H-pyrrole-2,5-dione can be converetd to (meso)-N-benzyl-3,4dihydroxy-2,5-pyrrolidinedione using 1.3 equiv.…”
Section: Introductionmentioning
confidence: 99%
“…of NaIO 4 and 0.8 mol% of Ru III Cl 3 in 73.3% yield. 6 In recent years, considerable advances have been made in the development of atom-efficient and environmentally friendly catalytic cis-dihydroxylation methods employing H 2 O 2 , 1 most notably, in the use of iron pyridyl-amine complexes, by Que et al, 7 manganese complexes by De Vos et al 8 and Feringa et al 9 and others 10 and ruthenium complexes by Che et al 11 With the [Mn III 2 O(RCO 2 ) 2 (tmtacn) 2 ] 2+ catalysts 12 we have reported recently, 9b-e the cis-dihydroxylation of electron rich cis-alkenes was achieved with over 8000 turnovers to the cis-diol product of cis-cyclooctene and near complete atom efficiency in the oxidant H 2 O 2. By contrast, this system shows little activity with electron deficient alkenes such as diethyl fumarate.…”
Section: Introductionmentioning
confidence: 99%